2018
DOI: 10.1038/s41419-018-0788-2
|View full text |Cite
|
Sign up to set email alerts
|

Ricolinostat (ACY-1215) suppresses proliferation and promotes apoptosis in esophageal squamous cell carcinoma via miR-30d/PI3K/AKT/mTOR and ERK pathways

Abstract: Ricolinostat (ACY-1215), a first-in-class selective HDAC6 inhibitor, exhibits antitumor effects alone or in combination with other drugs in various cancers. However, its efficacy in esophageal cancer remains unclear. In this study, we found that the high expression of HDAC6 was associated with poor prognosis in esophageal squamous cell carcinoma (ESCC) tissues. Then, we identified that ACY-1215 significantly inhibited cellular proliferation in ESCC, and caused G2/M phase arrest and apoptosis. We further demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 40 publications
3
46
0
1
Order By: Relevance
“…For example, Wang et al reported that hydrogen sulfide activated PI3K/AKT/mTOR pathway to promote cancer progression in HCC 30 . In esophageal squamous cell carcinoma, ricolinostat (ACY-1215) could suppressed proliferation and promotes apoptosis via PI3K/AKT/mTOR pathway 31 . Moreover, studies by Wang et al demonstrated that PI3K/AKT/mTOR signaling pathway could promote autophagy of hepatocellular carcinoma cells regulated by Alpha-fetoprotein (AFP) 32 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al reported that hydrogen sulfide activated PI3K/AKT/mTOR pathway to promote cancer progression in HCC 30 . In esophageal squamous cell carcinoma, ricolinostat (ACY-1215) could suppressed proliferation and promotes apoptosis via PI3K/AKT/mTOR pathway 31 . Moreover, studies by Wang et al demonstrated that PI3K/AKT/mTOR signaling pathway could promote autophagy of hepatocellular carcinoma cells regulated by Alpha-fetoprotein (AFP) 32 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-30d was observed to be upregulated which may be directly suppressing PI3K regulatory subunit 2 (PIK3R2). Additionally, the effects caused by PI3K/AKT signaling inhibition, apoptosis and cell cycle arrest have been reported to have been partially restored by anti-miRNA-30d [141]. Many such studies have been published so far, which reveal miRNAs as tumor suppressors or oncogenes (Table 1).…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%
“…Unfortunately, the poor pharmacokinetic properties limited its application. In contrast, another well-known HDAC6 selective inhibitor ACY-1215 has a rigid and less cumbersome capping group contributing to its HDAC6 selectivity; nevertheless, it exhibited a selectivity index of only about 10 against HDAC1-3 (21). We designed and synthesized a series of novel HDACis with the N-phenylpiperidine-1-carboxamide as the skeleton in this work.…”
Section: Cell Proliferation Inhibitionmentioning
confidence: 99%